INKLUSIVISME GURU PENDIDIKAN AGAMA ISLAM (Studi atas Pandangan Guru PAI tentang Konsep Tasamuh di SMK NU Lamongan, Mts Putra Putri Lamongan, SD NU Banat-Banin Lamongan) - A. Samsul Ma'arif (Universitas Islam Lamongan, 2019)
Educational institutions in which there is an educational process, have a function not only in the aspect of developing science, but also have a mission to improve the quality of personality through good character. In this position, the teacher has a role in instilling inclusive values (tasamuh) in the learning process that can be applied in everyday life as well as the process in developing the potential of their students. Each educational institution or each teacher will have different tasamuh values in each habituation or teaching. Get used to communicating with others using the language of unity, namely Indonesian, helping each other, not blaming others, especially fellow Muslims, especially other religions, and respecting different principles and respecting others. This study focuses on the views of Islamic Education teachers about the concept of tasamuh and the actualization of the tasamuh attitude of Islamic Education teachers in the learning process at SMK NU Lamongan, MTs Putra Putri Lamongan, SD NU Banat-Banin Lamongan. This study uses a qualitative research method with a phenomenological approach. This study shows that teachers play a role in developing tolerant attitudes to students in the school environment, social groups and even the community, through habituation and learning Islamic Education. The teacher's perspective on inclusive attitudes also plays a role in shaping the personality of students to be more open and respect all differences.